Impacts of the 2020 Siberia heatwaves on vegetation productivity - Park Sung-Bin; Park, Chang Eui; Song, Eun-Ji; Park, Sang Seo (제4회 KGU 연례학술대회 초록집, 2023)
Long-lasting heatwaves swept northern Siberia from January to June 2020. Previous studies reported anomalously warm spring increased spring vegetation CO2 uptake and leaf area index. However, annual net CO2 uptake and late season vegetation greenness were reduced due to soil moisture deficits in late summer, which were caused by early-season moisture depletion. Spatial distribution of annual Gross Primary Production (GPP) anomalies during the heatwaves were contrasting between western and eastern Siberia, however it is relatively understudied compared to the vegetation greenness and net CO2 uptake. To better understand GPP anomalies before and after the heatwaves, we re-examined growing season GPP and its relevant proxies along with meteorological variables, by splitting the Siberia regions into west and east. We analyzed monthly and annual GPP anomalies relative to the long-term mean (2001- 2021) from the Orbiting Carbon Observatory-2 (OCO2) Solar-induced Chlorophyll Fluorescence (SIF) product version 2 (GOSIF-GPP). We also estimated GPP proxy, such as carbon uptake period (CUP) and maximum GPP (GPPmax) from this dataset. To examine vegetation greenness, we utilized SIF from GOSIF. For abiotic variables, we used 2m temperature, soil moisture, surface turbulent fluxes, and solar radiation from the ECMWF Reanalysis v5-Land (ERA5-Land), and the Multi-Source Weighted-Ensemble Precipitation. All data were aggregated monthly and regraded to spatial resolution of 0.25 degrees. GPP increased more in western Siberia than in eastern side during May, coinciding with the areas of positive temperature anomalies. Vegetation production in western Siberia was still positive in June, despite weak surface cooling that may be caused by increased precipitation. Soil moisture depletion seems not severe and may not affect vegetation production in this month. However, July GPP reduction was more substantial in eastern Siberia than in western Siberia. This was consistent with meteorological patterns (high rainfall and low downward incoming solar radiation anomalies). Anomalously warm temperatures and moisture deficits mostly disappeared in June and July. However, high temperature and strong incoming solar radiation accompanied with low precipitation and low soil moisture in August may generate soil moisture deficits. We will further discuss the possible reasons why the negative GPP anomalies in Siberia were less severe even under hot and dry conditions, as well as the impact of heatwave legacy on vegetation production.